Direct vs. redirected admission of critically ill children to PICU after interfacility transfer: a retrospective cohort study - Halgren, C.; Annich, G. M.; Maratta, C. (Frontiers in Pediatrics, 2024)
Background: Critically ill children must often be transported long distances for access to critical care resources in Canada. This study aims to describe and compare characteristics and outcomes in patients presenting in the community and requiring inter-facility transport and admission to a Pediatric Intensive Care Unit (PICU). Methods: This is a retrospective cohort study of children admitted to the ICU at the Hospital for Sick Children from 2016 to 2019 after inter-facility transport. Characteristics and outcomes were compared between children admitted to the PICU within 24h from their initial critical care transport request, and children admitted after initial redirection to a non-ICU care setting, 24-72h from request. The primary outcome was severity of illness at PICU admission. Secondary outcomes included duration of mechanical ventilation, organ dysfunction, PICU length of stay and mortality. Results: A total of 2730 patients were admitted after inter-facility transport to either the medical/surgical or cardiac ICU within 72h of initial critical care transport request. Of these children, 2559 (94%) were admitted within 24h and 171 (6%) were admitted between 24-72h. Children admitted after initial redirection were younger and residing in more rural centers. Children who were initially redirected had lower severity of illness (PRISM-IV median score 3 vs 5, p=0.047) and lower risk of mortality. Interpretation: Initial redirection to a non-ICU care setting rather than directly admitting to the PICU did not result in increased severity of illness or mortality. This study highlights the need to better understand which factors influence disposition decision-making at the time of initial transport request. Further research should focus on the impact of transport factors on clinical outcomes after PICU admission.